A novel small molecule, CU05-1189, targeting the pleckstrin homology domain of PDK1 suppresses VEGF-mediated angiogenesis and tumor growth by blocking the Akt signaling pathway - Park, Jeongeun; Zhang, Haiying; Kwak, Hyun Jung; Gadhe, Changdev Gorakshnath; Kim, Yeomyeong; Kim, Hyejeong; Noh, Minyoung; Shin, Dongyun; Ha, Sang-Jun; Kwon, Young-Guen (Frontiers in Pharmacology, 2023)
Inhibition of angiogenesis is considered a promising therapeutic approach for cancer treatment. Our previous genetic research showed that the use of a cell-penetrating peptide to inhibit the pleckstrin homology (PH) domain of 3-phosphoinositide-dependent kinase 1 (PDK1) was a viable approach to suppress pathological angiogenesis. Herein, we synthesized and characterized a novel small molecule, CU05-1189, based on our prior study and present evidence for the first time that this compound possesses antiangiogenic properties both in vitro and in vivo. The computational analysis showed that CU05-1189 can interact with the PH domain of PDK1, and it significantly inhibited vascular endothelial growth factor (VEGF)-induced proliferation, migration, invasion, and tube formation in human umbilical vein endothelial cells without apparent toxicity. Western blot analysis revealed that the Akt signaling pathway was specifically inhibited by CU05-1189 upon VEGF stimulation, without affecting other VEGF receptor 2 downstream molecules or cytosolic substrates of PDK1, by preventing translocation of PDK1 to the plasma membrane. We also found that CU05-1189 suppressed VEGF-mediated vascular network formation in a Matrigel plug assay. More importantly, CU05-1189 had a good pharmacokinetic profile with a bioavailability of 68%. These results led to the oral administration of CU05-1189, which resulted in reduced tumor microvessel density and growth in a xenograft mouse model. Taken together, our data suggest that CU05-1189 may have great potential and be a promising lead as a novel antiangiogenic agent for cancer treatment.